N-Acetylcysteine an Allium Plant Compound Improves High-Sucrose Diet-Induced Obesity and Related Effects - Souza, Gisele A. [UNESP]; Ebaid, Geovana Xavier [UNESP]; Seiva, Fabio R. F. [UNESP]; Rocha, Katiucha H. R. [UNESP]; Galhardi, Cristiano Machado [UNESP]; Mani, Fernanda [UNESP]; Novelli, Ethel L. B. [UNESP] (Hindawi Publishing Corporation, 2011)
This study was designed to determine whether N-acetylcysteine (NAC, C(5)H(9)-NO(3)S), a compound from Allium species may be used as a complementary therapeutic agent, to inhibit high-sucrose induced-obesity and its effects on glucose tolerance, in vivo low-density lipoprotein (LDL)-oxidation and serum oxidative stress in rats. Initially, 24 male Wistar rats were divided into two groups: controls receiving standard chow (C, n = 6) and those receiving high-sucrose diet (HS, n = 18). After 22 days, (HS) group was divided into three groups (n = 6/group); (HS-HS) continued to eat high-sucrose diet and water; (HS-N) continued to eat high-sucrose diet and received 2 mg l(-1)-NAC in its drinking water; (HS-CN) changing high-sucrose to standard chow and receiving 2 mg l(1)-NAC in its drinking water. After 22 days of the HS-group division (44 days of experimental period) body weight, body mass index and surface area were enhanced in HS-HS rats (P < .001). HS-HS rats had glucose intolerance, increased serum triacylglycerol (TG), very low-density lipoprotein (VLDL), oxidized-LDL (ox-LDL) and lipid-hydroperoxide (LH) than the others (P < .01). NAC in HS-N and HS-CN rats reduced the obesity markers, feed efficiency, LH and ox-LDL, as well normalized glucose response, TG and VLDL (P < .01) in these groups compared with HS-HS. Total antioxidant substances, GSH/GSSG ratio and glutathione-reductase, were higher in HS-N than in HS-HS (P < .01). In conclusion, NAC improved high-sucrose diet-induced obesity and its effects on glucose tolerance, lipid profile, in vivo LDL-oxidation and serum oxidative stress, enhancing antioxidant defences. The application of this agent may be feasible and beneficial for high-sucrose diet-induced obesity, which certainly would bring new insights on obesity-related adverse effects control.